A Comprehensive Preclinical Model Evaluating the Recombinant PRAME Antigen Combined With the AS15 Immunostimulant to Fight Against PRAME-expressing Tumors. Issue 8 (October 2015) - Gérard, Catherine; Baudson, Nathalie; Ory, Thierry; Segal, Lawrence; Louahed, Jamila
Abstract : The PRAME tumor antigen is a potential target for immunotherapy. We assessed the immunogenicity, the antitumor activity, and the safety and the tolerability of a recombinant PRAME protein (recPRAME) combined with the AS15 immunostimulant (recPRAME+AS15) in preclinical studies in mice and Cynomolgus monkeys. Four groups of 12 CB6F1 mice received 4 injections of phosphate-buffered saline (PBS), recPRAME, AS15, or recPRAME+AS15. Immunized mice were injected with tumor cells expressing PRAME (CT26-PRAME) 2 weeks or 2 months after the last injection. The mean tumor surface was measured twice a week. Two groups of 10 monkeys received 7 injections of saline or recPRAME+AS15. T-cell responses were measured by flow cytometry using intracellular cytokine staining (ICS). In CB6F1 mice, repeated injections of recPRAME+AS15 induced high PRAME-specific antibody titers and mostly CD4 + T cells producing cytokines. This immune response was long-lasting in these animals and was associated with protection against a challenge with PRAME-expressing tumor cells (CT26-PRAME) applied either 2 weeks or 2 months after the last injection; these data indicate the induction of an immune memory. In HLA-A02.01/HLA-DR1 transgenic mice, recPRAME+AS15 induced both CD4 + and CD8 + T-cell responses, indicating that this antigen can be processed by the human leukocyte antigen and is potentially immunogenic in humans. In addition, a repeated-dose toxicity study in monkeys showed that 7 biweekly injections of recPRAME+AS15 were well tolerated, and induced PRAME-specific antibodies and T cells. In conclusion, these preclinical data indicate that repeated injections of the PRAME cancer immunotherapeutic are immunogenic and have an acceptable safety profile. Abstract : Supplemental Digital Content is available in the text.